2011
DOI: 10.1093/pcp/pcr015
|View full text |Cite
|
Sign up to set email alerts
|

Duplicated C-Class MADS-Box Genes Reveal Distinct Roles in Gynostemium Development in Cymbidium ensifolium (Orchidaceae)

Abstract: The orchid floral organs represent novel and effective structures for attracting pollination vectors. In addition, to avoid inbreeding, the androecium and gynoecium are united in a single structure termed the gynostemium. Identification of C-class MADS-box genes regulating reproductive organ development could help determine the level of homology with the current ABC model of floral organ identity in orchids. In this study, we isolated and characterized two C-class AGAMOUS-like genes, denoted CeMADS1 and CeMADS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 55 publications
3
55
1
1
Order By: Relevance
“…The D-lineage gene expression pattern in orchids differs from that of LMADS2 (L. longiflorum) and HoMADS1 (H. orientalis), which were expressed exclusively in ovules (Tzeng et al, 2002;Xu et al, 2004). Although the orchid C-and D-lineage genes are expressed in column and ovaries, the expression level of D-lineage genes is higher in ovaries at late flower development stages in C. ensifolium, O. italica, and Phalaenopsis hybrid (Acri-Nunes-Miranda and Mondragón-Palomino, 2014; Salemme et al, 2013;Wang et al, 2011). These results indicate that orchid Cand D-lineage genes have important roles in column and ovule development.…”
Section: -3) Orchid Flowersmentioning
confidence: 83%
See 1 more Smart Citation
“…The D-lineage gene expression pattern in orchids differs from that of LMADS2 (L. longiflorum) and HoMADS1 (H. orientalis), which were expressed exclusively in ovules (Tzeng et al, 2002;Xu et al, 2004). Although the orchid C-and D-lineage genes are expressed in column and ovaries, the expression level of D-lineage genes is higher in ovaries at late flower development stages in C. ensifolium, O. italica, and Phalaenopsis hybrid (Acri-Nunes-Miranda and Mondragón-Palomino, 2014; Salemme et al, 2013;Wang et al, 2011). These results indicate that orchid Cand D-lineage genes have important roles in column and ovule development.…”
Section: -3) Orchid Flowersmentioning
confidence: 83%
“…Subsequent duplication occurred among the orchid C-lineage genes in Epidendroideae and Orchidoideae, and there are two types of C-lineage genes in Cymbidium ensifolium (CeMADS1 and CeMADS2) and the Phalaenopsis hybrid cultivar 'Athens' (PhaMADS8 and PhaMADS10). Gene expression analyses in some orchid species such as Phalaenopsis equestris, C. ensifolium, and Orchis italica showed that the C-and D-lineage genes were expressed primarily in the column and ovaries (Acri-Nunes-Miranda and Mondragón-Palomino, 2014; Chen et al, 2012b;Hsu et al, 2010;Salemme et al, 2013;Skipper et al, 2006;Song et al, 2006;Wang et al, 2011;Xu et al, 2006). The D-lineage gene expression pattern in orchids differs from that of LMADS2 (L. longiflorum) and HoMADS1 (H. orientalis), which were expressed exclusively in ovules (Tzeng et al, 2002;Xu et al, 2004).…”
Section: -3) Orchid Flowersmentioning
confidence: 99%
“…There have been multiple duplication events within the C-class lineage (13) followed by partial redundancy (14)(15)(16), potential or proven subfunctionalization (17)(18)(19)(20)(21)(22)(23)(24), or switching of functional equivalence among duplicates in different species (25). Even when a single gene is present, alternative transcripts are a source of genetic variation (14).…”
mentioning
confidence: 99%
“…Less common are aberrations referring to the number of the stamens (Bateman and Rudall 2006). As some teratologia are genetically stable and inheritable, some cultivars have been bred which have commercial but also historical-cultural value, particularly well-known in Vanda falcata (Duttke et al 2012, Anonymous 2014 and several Cymbidium species (Wang et al 2011).…”
mentioning
confidence: 99%